Relationship between English self-efficacy and language learning strategies among Peruvian university students: the mediating role of academic self-efficacy - Saez-Zevallos, Nataly Susan; Cunza-Aranzábal, Denis Frank; Abanto-Ramírez, Carlos D.; Montalvo-Apolín, Danitza Elfi (Frontiers in Education, 2025)
IntroductionThis study investigates the mediating role of academic self-efficacy in the relationship between English self-efficacy and language learning strategies among Peruvian university students.MethodAn explanatory cross-sectional design was employed, utilizing a convenience sample of 610 participants. The instruments used included the Strategy Inventory for Language Learning (SILL), the English Self-Efficacy Scale (EAI), and the Perceived Academic Situational Self-Efficacy Scale (EAPESA). The reliability and internal structure of each scale were verified, and the SILL was validated. Descriptive and correlation analyses between variables were conducted, followed by path and mediation analyses.ResultsThe proposed model showed adequate fit indices (χ2 = 178, df = 33, p < 0.001, CFI = 0.964, TLI = 0.951, RMSEA = 0.085 [CI 90%: 0.073; 0.097]). The indirect effect of English self-efficacy on language learning strategies through academic self-efficacy was significant (β = 0.202, p < 0.001, 95% CI [0.144, 0.261]), indicating that 31.61% of the total effect (direct plus indirect) of English self-efficacy on language learning strategies is explained by this indirect effect.ConclusionThe results highlight the importance of academic self-efficacy as a mechanism through which English self-efficacy enhances the use of language learning strategies.